Influence of reservoir minerals and ethanol on catalytic aquathermolysis of heavy oil. (1st January 2022) - Zhou, Zhichao; Slaný, Michal; Kuzielová, Eva; Zhang, Wangyuan; Ma, Liwa; Dong, Sanbao; Zhang, Jie; Chen, Gang
Highlights: The influence of different alcohols on the aquathermolysis of heavy oil was studied. Sodium bentonite has the best catalytic effect for clay minerals. Ferrous sulfide shows the best catalytic effect for non-clay minerals. The viscosity reduction rate of crude oil reach to 87.32 % after aquathermolysis. Abstract: In this paper, the effect of different types of minerals and alcohols as hydrogen donors on the catalytic aquathermolysis of heavy oil was investigated. The best catalytic effect showed sodium clay. Methanol was demonstrated as the most suitable to enhance viscosity reduction efficiency. Under the optimal conditions of the catalytic aquathermolysis, the viscosity reduction rate can reach 87.32 % in comparison with the original oil. Differential scanning calorimetry (DSC), Fourier Transform Infrared Spectrometry (FTIR), Thermogravimetric Analysis (TGA), Elemental analysis, and Gas chromatography-mass spectrometry (GC–MS) were used to study the changes occurring during the catalytic aquathermolysis of crude oil. In addition, several different model compounds (1-octene, thiophene, phenol, pyridine, quinoline, benzothiophene, and nonylphenol) were selected to simulate the chemical changes of crude oil components and to propose the reaction mechanisms.